Penerapan activity of daily living (adl) terhadap insomnia pada lansia - Nurhayati, Nurhayati (JOURNAL OF Tropical Medicine Issues, 2024)
Background: Insomnia is the most common sleep disorder in the elderly, which is characterized by the inability to initiate sleep, maintain sleep, wake up too early or sleep that is not refreshing. Handling is done by encouraging daily activities such as eating, bathing, gardening etc. Purpose: To describe the implementation of Activity of Daily Living (ADL) in the elder. Method: This scientific paper uses a descriptive scientific paper design. Respondents were two elderly women who were taken using interview techniques. The instrument used to measure the level of insomnia using a questionnaire measuring insomnia in the elderly. Results: Both subjects experienced a decrease from moderate to mild insomnia. Conclusion: Can make the application of Activity of Daily Living (ADL) a non-pharmacological treatment that can be done every day to improve sleep quality. Keyword: Activity of Daily Living; Elderly; Insomnia. Pendahuluan: Insomnia adalah gangguan tidur paling sering terjadi pada lanjut usia, yang ditandai dengan ketidakmampuan untuk mengawali tidur, mempertahankan tidur, bangun terlalu dini atau tidur yang tidak menyegarkan. Penanganan yang dilakukan yaitu dengan mendorong aktivitas-aktivitas sehari-hari seperti makan, mandi, berkebun dll. Tujuan: Untuk mengetahui gambaran penerapan Activity of Daily Living (ADL) pada lansia. Metode: Desain karya tulis ilmiah deskriptif. Responden berjumlah dua orang lansia yang berjenis kelamin perempuan yang diambil menggunakan tekhnik wawancara. Instrumen yang digunakan untuk mengukur tingkat insomnia menggunakan kuesioner, pengukuran insomnia pada lansia. Hasil: Pada kedua subjek mengalami penurunan dari insomnia sedang ke ringan. Simpulan: Dapat menjadikan penerapan Activity of Daily Living (ADL) sebagai pengobatan non farmakologi yang dapat dilakukan setiap hari untuk peningkatan kualitas tidur. Kata Kunci: Activity of Daily Living; Insomnia; Lansia.